Ethanol Production Comparison from Agricultural Waste of Cellulose Source Within Hydrolysis Hcl and Cellulose Enzyme - Indra Masmur; Clairine Clairine; Mega Evelin Rajagukguk; Teti Purwita Sari; Elvri Melliaty Sitinjak (Universitas Negeri Medan, 2022)
The production of Ethanol has been utilized through the process of cellulose isolation from agricultural waste such as corn husk, rice straw and rice husk. Isolation of cellulose with pretreatment delignification using, NaOH 2% to produces cellulose of corn husk 16,6921 g (22,25%), rice straw 16,9021 g (22,53%) and rice husk 16,3691 g (21,85%) then analyzed the functional groups using FT-IR and SEM analysis. Cellulose as much as 2 g is hydrolyzed using HCl 30% and cellulase enzymes to obtain sugar that is qualitatively tested with Benedict and Tollens reagent and quantitatively tested with Luff Schoorl method and produces highest sugar content of rice husk 8,64% and 10,95%. The next stage sugar of hydrolysis will be fermented using yeast (Saccharomyces cerevisiae) with 6 days, and then distilled at a temperature of 78-80oC. Ethanol was calculated by the potassium dichromate oxidation method to gave highest result from agricultral waste of ethanol chemical 5,97% and enzymatic 6,89% is rice husk.